Functional engineering of OprF-OprI-PopB as a chimeric immunogen and its cross-protective evaluation with GM-CSF against Pseudomonas aeruginosa: A comprehensive immunoinformatics evaluation. (2021) - Sabzehali, Fattaneh; Rahimi, Hamzeh; Goudarzi, Hossein; Goudarzi, Mehdi; Yoosefi Izad, Mohammad Hossein; Salimi Chirani, Alireza; Jalali, Seyed Amir; Faghihloo, Ebrahim
Abstract: Pseudomonas aeruginosa ( P. aeruginosa ) is an opportunistic pathogen in burns, cystic fibrosis, hospitalized and immunodeficiency patients. By in-silico algorithms an effective vaccine was designed from outer membrane proteins (OprF and OprI) and type 3 secretion systems (PopB) of P. aeruginosa to combat laboratory barriers and store time, reduce cost, and achieve higher performances. The aim of this study was the construction, expression, and evaluation of recombinant protein containing OprF, OprI, and PopB (FIB). We combined the in-silico immunoinformatics, homology modeling, molecular docking and molecular dynamics (MD) simulations. The linear and conformational B-cell epitopes and T-cell epitopes in the 172 subunit candidates were investigated and the best 16 of them was recognized to create a multi-epitope vaccine. Ultimately, we realized stable interactions between the epitopes of "NATAEGRAINRRVE" OprF in 305–318 and "KAANRQADVQESRAD" PopB in the position of 730–744 as ligands and HLADRB1*04:01 as a receptor. This proposed vaccine constructs a 794aa multi-epitope vaccine containing 66 B-cell epitopes and 106 T-cell epitopes. The levels of IgG (G1, G2a, and G2b) and IgA antibody titers and the level of IL-17, IFN-γ, and IL-4 cytokines were evaluated before and after challenge using the enzyme-linked immunosorbent assay (ELISA) method. Due to enhancing the active immune response, FIB antigen was formulated with Granulocyte-macrophage colony-stimulating factor (GM-CSF) as a potent adjuvant. The comparison of IgG1, IgG2a, IgG2b antibodies, cytokines IL-17, IL-4, and IFN-γ levels indicated a higher rate of Th1 and Th2 oriented responses against P. aeruginosa chimeric FIB antigen. The FIB antigen was a potent IgA inducer in the presence of adjuvant. Also, the immunogenic response against FIB and FIB-GMCSF revealed the useful property of GM-CSF in enhancing the humoral and cell-mediated immune response. Our findings highlighted that FIB plus GM-CSF immunization would be useful as an immunogenic substance for treatment against P. aeruginosa infections.